Aggregation-induced emission nanoprobe assisted ultra-deep through-skull three-photon mouse brain imaging. (August 2022) - He, Mubin; Li, Dongyu; Zheng, Zheng; Zhang, Hequn; Wu, Tianxiang; Geng, Weihang; Hu, Zhengwu; Feng, Zhe; Peng, Shiyi; Zhu, Liang; Xi, Wang; Zhu, Dan; et al.
Abstract: Optical microscopy has enabled in vivo monitoring of brain structures and functions with high spatial resolution. However, the strong optical scattering in turbid brain tissue and skull impedes the observation of microvasculature and neuronal structures at a large depth. Herein, we proposed a strategy to overcome the influence induced by the high scattering effect of both skull and brain tissue via the combination of skull optical clearing (SOC) technique and three-photon fluorescence microscopy (3PM). The visible-NIR-II compatible skull optical clearing agents (VNSOCA) we applied reduced the skull scattering and water absorption in long wavelength by refractive index matching and H2 O replacement to D2 O respectively. 3PM with the excitation in the 1300-nm window reached 1.5 mm cerebrovascular imaging depth in cranial window assisted by a kind of bright aggregation-induced emission (AIE) nanoprobe we developed with a large three-photon absorption cross section. Combining the two advanced technologies together, we achieved so far the largest cerebrovascular imaging depth of 1.0 mm and neuronal imaging depth of> 700 µm through intact mouse skull. Dual-channel through-skull imaging of both brain vessels and neurons was also successfully realized, giving an opportunity of non-invasively monitoring the deep brain structures and functions at single-cell level simultaneously. Graphical Abstract: ga1 Highlights: Skull optical clearing and three-photon microscopy were combined to reduce scattering interference. Aggregation-induced emission nanoprobes with extremely large three-photon absorption section benefit deep imaging. Through-skull three-photon mouse cerebrovascular imaging achieved the largest 1.0 mm imaging depth.